From Participation To Transformation: Outcomes Of Inclusive Governance For Marginalized Communities In Rural Indonesia (International Journal of Environmental Sciences, 2025)
Public engagement has been widely recognized as a cornerstone of inclusive governance and sustainable development, yet empirical studies often overlook its tangible outcomes, particularly in rural and marginalized contexts. This study analyzes the outcomes of public engagement in the Estungkara Program, implemented in Tompobulu District, Maros Regency, Indonesia. Guided by the Direct Public Engagement Framework (Nabatchi & Amsler, 2014), the research explores how participatory practices influence individual empowerment, community solidarity, and institutional reform. A qualitative case study approach was employed, involving in-depth interviews, observations, and document analysis with local government officials, community leaders, and marginalized groups. Findings reveal that the Estungkara Program has contributed significantly to improving access to basic services and civil documentation at the individual level, strengthening social capital and collective action at the community level, and enhancing transparency and legitimacy in village governance at the institutional level. These outcomes demonstrate that participatory initiatives, when designed and implemented inclusively, can generate transformative impacts beyond formal consultation. The study contributes to the global discourse on inclusive governance by highlighting the importance of evaluating outcomes, and provides practical lessons for policymakers and practitioners seeking to design participatory frameworks that address structural barriers and empower marginalized communities.